Phase I Randomized Study of a Tetravalent Dengue Purified Inactivated Vaccine in Healthy Adults from Puerto Rico - Diaz, Clemente; Lin, Leyi; Martinez, Luis J.; Eckels, Kenneth H.; Campos, Maribel; Jarman, Richard G.; De La Barrera, Rafael; Lepine, Edith; Toussaint, Jean-François; Febo, Irma; Innis, Bruce L.; Thomas, Stephen J.; et al. (The American journal of tropical medicine and hygiene, 2018)
The safety and immunogenicity of four adjuvanted formulations of an investigational tetravalent dengue purified inactivated vaccine (DPIV) were evaluated in a predominantly dengue-primed population in Puerto Rico. In this placebo-controlled, randomized, observer-blind, phase I trial, 100 healthy adults were randomized 1:1:1:1:1 to receive DPIV at Day (D)0 and D28 (1 μg per dengue virus [DENV] type 1–4 adjuvanted with either alum, AS01 E or AS03 B , or 4 μg per DENV type adjuvanted with alum) or saline placebo. Functional antibody responses were assessed using a microneutralization assay at D56, Month (M)7, and M13. All DPIV formulations were well tolerated and no safety signals were identified through M13. The M13 according-to-protocol (ATP) immunogenicity cohort included 83 participants. The ATP analysis of immunogenicity was performed only on the 78 subjects seropositive for ≥ 1 DENV type at baseline: 69 tetravalent, three trivalent, two bivalent, and four monovalent. In all DPIV groups, geometric mean antibody titers (GMTs) increased from D0 to D56 and waned modestly through M13, while remaining well above prevaccination levels. The 4 μg + alum and the AS01 E - and AS03 B -adjuvanted formulations were highly immunogenic, with M13-neutralizing antibody GMTs against all four DENV types above 1,000. M13/D0 GMT ratios were highest in the 1 μg + AS03 B group (ranging 3.2–3.7 depending on the DENV type). These results encourage continued clinical development of DPIV (ClinicalTrials.gov: NCT01702857).